Regulatory T-Cells in Treatment of Type-1 Diabetes: Types and Approaches - Mahinder Paul; Neenu Jacob; Naresh Sachdeva (Diabetes Research, 2015)
Regulatory T-cells (Tregs) play important role in regulation of immune responses to self-antigens. Alterations in frequency and function of Tregs have been reported in Type 1 Diabetes (T1D) subjects. Tregs have the potential to prevent destruction of pancreatic beta cells by targeting effector T-cells (Teff) and other immune cells causing inflammation. Therefore, strategies to increase Treg cell numbers and function are being explored as potential immunotherapeutic approaches in treating T1D. Today, several groups are involved in exploring different Treg cell types, sources, induction procedures and experimental systems in pursuit of generation of highly efficacious and stable Tregs for their clinical applications. Various protocols have been developed for the induction and expansion of islet antigen specific Tregs and polyclonal Tregs. Studies have shown that antigen specific Tregs are required at less number and are more efficient than polyclonal Tregs in suppressing autoimmune diabetes and they do not cause generalized immune suppression. Alternatively, generation of colonic Tregs (cTregs) has also gathered attention in recent years as an approach to limit pancreatic inflammation via gut induced tolerance. With a definitive treatment for T1D still elusive, application of Tregs as a part of combination therapy seems promising in treatment of T1D.